The role of culture in the sustainable development of voivodships in Poland - Grażyna Krzyminiewska; Hanna Pondel (Economic and Environmental Studies (E&ES), 2017)
The purpose of the study is an attempt to assess the importance of culture for the sustainable development of Polish voivodships. For the purpose of this research, a taxonomic method was used to distinguish areas similar to one another in terms of the characteristics examined and to group them into regions with similar development conditions. On the basis of the analysis of the source data and the set of synthetic indicators of sustainable development it can be stated with certainty that cultural activities (in terms of institutional approach) taken in Polish voivodships are important for the level of their sustainability.
Keywords: Q01; R58; 330; culture; sustainable development; voivodships; taxonomic method